A review of the mechanism, diagnosis, and treatment of Naegleria fowleri infection - Dai, Ling; Guo, Xin-Ru; Chen, Xu-Rui; Ma, Ming-Hao; Liu, Zi-Han; Lai, Juan; Lu, Jun; Feng, Ming; Liu, Xi-Xia; Yang, Sheng-Hui (Frontiers in Microbiology, 2025)
Naegleria fowleri is a rare pathogen responsible for primary amoebic meningoencephalitis (PAM), a fatal central nervous system infection characterized by rapid clinical progression and an extremely high mortality rate. The existing diagnostic methods are insufficiently sensitive, and therapeutic options are minimal, making early recognition and intervention extremely challenging. This review systematically examines the biological characteristics and pathogenic mechanisms of this pathogen, as well as current diagnostic and treatment strategies, with a particular focus on the groundbreaking applications of emerging technologies such as metagenomic next-generation sequencing (mNGS) in the diagnosis of difficult-to-treat infections. The aim is to provide theoretical support and practical guidance for rapid identification, accurate diagnosis, and timely intervention in clinical practice, serving as a reference for the prevention and treatment of N. fowleri infections.